PENGEMBANGAN PROGRAM PEMBANGUNAN MASYARAKAT DESA DI ERA OTONOMI DAERAH - Mu'man Nuryana (Politeknik Kesejahteraan Sosial, 2003)
(Accelerating Rural Program Development in The Decentralisation Ere.) - Suatu Pendekatan Kebijakan Penciptaan Lapangan kerja.Â Rural employment creation policies should be an influential for rural economic developmentwhere more than 65% of the Indonesia's population reside in rural areas. However, since ruralareas are economically divided into three categories-integrated, intermediate, remote areas-the idea of differentiating employment creation policies could be relevant choices. The basic ideas of employment creation policies are direct aid, indirect aid, human resources, and infrastructure. Which one of those four policies appropriate for certain rural area, it depends on the type of rural area. This article demonstrates how differentiated rural employment policies and different type of rural areas should be in the context of national economy in the era of local autonomy in Indonesia.Key Words: intergrated, intermediate, remote, direct, indirect, human resources, infrastructure